The role of off-farm employment in promoting sustainable farm development through integrated pest management technology adoption - Jinglin Ke; Hancheng Dan; Qing Wang; Amar Razzaq (Frontiers in Sustainable Food Systems)
This study explores the impact of off-farm employment on the adoption of Integrated Pest Management (IPM) technology among farmers in rural China, with a focus on sustainable farm development. Utilizing micro-survey data and applying an endogenous switching Probit model within a counterfactual analysis framework, the research examines how off-farm employment influences the likelihood of adopting IPM technology. The findings reveal that 67.84% of farmers have adopted IPM technology, while 32.16% have not. The counterfactual analysis indicates that if farmers with off-farm employment did not engage in off-farm activities, their probability of adopting IPM technology would decrease by 71.57%. Conversely, if farmers without off-farm employment were to engage in off-farm activities, their probability of adopting IPM technology would increase by 76.95%. Key factors influencing off-farm employment include age, education level, number of elderly in the household, membership in a cooperative, number of land plots, village topography, and the number of family members and relatives working in government or public institutions. In addition, age, personal health status, number of household laborers, membership in a cooperative, number of land plots, village topography, and ecological cognition significantly affect the adoption of IPM technology. The study suggests that optimizing industrial structure, improving the rural employment market, enhancing the role of farmers’ professional cooperatives, strengthening education and training efforts, and increasing publicity efforts can collectively improve the adoption of IPM technology. These strategies contribute to sustainable farm development and better environmental outcomes.